The C-terminal regions of the GLP-1 and GIP receptors are not the key determinants of their differential arrestin recruitment but modulate the rate of receptor endocytosis - Al-Zaid, Bashaier; Al-Sabah, Suleiman (Frontiers in Pharmacology, 2025)
Introduction: Glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) are important regulators of metabolism and mediate the incretin effect. This glucose-dependent potentiation of insulin secretion is severely impaired in patients with type-2 diabetes mellitus. While pharmacological doses of GLP-1 can overcome this impairment, the same is not true for GIP. The reasons for this are unclear. However, differences in the signalling profiles of the GLP-1 and GIP receptors (GLP-1R and GIPR) may contribute. GLP-1R and GIPR are closely related G protein-coupled receptors but differ in their ability to recruit arrestin, GIPR being relatively poorer. Furthermore, these receptors have been reported to utilize different mechanisms to undergo agonist-induced internalization.Methods: This study aimed to identify the role of the C-terminal region of the two receptors in their differing signalling behaviour using chimeric receptors where the C-terminal tail of one receptor was replaced with that of the other.Results: Replacement of the C-terminal tail had only limited effects on G protein and arrestin recruitment to either receptor. GIP-stimulated internalisation of GIPR occurred at a significantly (P < 0.001) slower rate than GLP-1-stimulated internalisation of GLP-1R. Replacement of the C-terminal tail of GIPR with that of GLP-1R significantly (P < 0.05) increased the internalization rate but not to the rate of wild-type GLP-1R. The reciprocal substitution significantly (P < 0.005) decreased internalization rate.Conclusion: These data show that the C-terminal region of GLP-1R and GIPR is not the critical determinant of their differing ability to recruit arrestin but modulates receptor endocytosis.